Investigating High School Boys’ Academic Underachievement in Second Language Classrooms - Samra, Nora (2019)
This paper examines boys’ low-achievement in comparison with girls in the high school section at a private school in Dubai. The researcher includes four questions to be answered. The first question seeks to explore the factors that contribute to boys’ underachievement in an ESL setting. Furthermore, the second and third questions in this paper seek to conceive the teachers’, students’, and leaders’ perspectives of the reasons that impact the boys’ achievement in the ESL setting, while the fourth question seeks to explore if there is disparity in the quality of teaching between the boys’ and girls’ sections. This qualitative research adopts two main tools, which are observations and semi-structured interviews with teachers, leaders, and students. The findings of this case study explain why the boys’ term marks are lower than those of the girls. Some of these factors have to do with the teachers’ expectations in the boys’ abilities, while other factors are related to the students’ behaviours and the disruption they cause in the classrooms. Moreover, the findings show that the boys have low self-esteem, and they do not have high ambitions, as most of the interviewed boys plan to join the armed forces, which do not require high grades. In addition, the findings prove that there is no significant disparity in the quality of teaching between the boys’ and girls’ sections, but the disruptions of boys negatively affect the teaching and learning process. Another finding is that the assessment tools are not given sufficient attention by some teachers inside the classrooms. Moreover, there are some recommendations, which are based on the findings of this study, are listed in the “Conclusion Chapter,” such as raising the expectation in the boys’ abilities, maximizing the social workers’ roles in dealing with the boys’ behaviours and self-esteem, and increasing the professional development workshops for teachers. The significance of this case study comes from its connection to the UAE educational system, so it could help the educators to form or adapt policies to solve the problem of boys’ academic underachievement.